Simulation of the Tunka-Grande, TAIGA-Muon and TAIGA-HiSCORE arrays for a search of astrophysical gamma quanta with energy above 100 TeV. Issue 1 (March 2021) - Ternovoy, M; Kotovschikov, I; Budnev, N; Chiavassa, A; Dyachok, A; Gafarov, A; Garmash, A; Grebenyuk, V; Gress, O; Gress, T; Grishin, O; Grinyuk, A; et al.
Abstract: In the paper we present our simulation strategy of the Tunka-Grande, TAIGA-Muon, and TAIGA-HiSCORE arrays in the light of the problem of separation astrophysical high-energy gamma rays from the cosmic ray background. The paper contains a description of our simulation method, based on Geant4 and CORSIKA codes. We also present the prospect of future research with TAIGA (Tunka Advanced Instrument for cosmic rays and Gamma Astronomy) with using the simulation results.